Principles and Methods of Contrastive Phraseology (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
This article examines the current state and significance of contrastive phraseology in comparing genetically unrelated languages. It highlights the limited development of theoretical foundations in this field and emphasizes the importance of analyzing phraseological units through structural-semantic, typological, and cultural perspectives. The study reviews major scholarly contributions, outlines key methodological principles, and stresses the need for pedagogical and lexicographic resources—particularly for Uzbek-speaking learners. The article concludes that deeper comparative-typological research is essential for understanding interlingual phraseological correspondences and improving translation and teaching practices.